Qualitative research in medicine and healthcare: Is it subjective, unscientific or second class science? - Rahman, Sayeeda; Majumder, Md. Anwarul Azim (South East Asia Journal of Public Health, 2014)
South East Asia Journal of Public Health 2013; 3(1): 69-71 DOI: http://dx.doi.org/10.3329/seajph.v3i1.17715